Family Related Factors and Concurrent Heroin Use in Methadone Maintenance Treatment in China - Feng, Nan (Subst Use Misuse, 2018)
BACKGROUND: The use of heroin during Methadone Maintenance Treatment (MMT) is a challenging problem that contributes to poor treatment outcomes. Families may play an important role in addressing concurrent heroin use during MMT, especially in collectivist societies such as China. OBJECTIVES: In this study, we explored the relationship between family-related factors and concurrent heroin use during MMT in China. METHODS: This study was conducted at 68 MMT clinics in five provinces of China. There were 2,446 MMT clients in the analysis. Demographic information, MMT dosage, family members’ heroin use status, family support of MMT, family problem and self-reported heroin use were collected in a cross-sectional survey. The most recent urinalysis of opiate use was obtained from clinical records. RESULTS: Of the 2,446 participants, 533 (21.79%) self-reported heroin use in the previous seven days or had a positive urine morphine test result in the clinic record. Participants whose family member[s] used heroin were 1.59 times (95% CI: 1.17-, 2.15) more likely to use concurrently during treatment. Those with family members who totally support them on the MMT were less likely to use (AOR: 0.75, 95% CI: 0.60, 0.94). Having more family problems was positively associated with concurrent heroin use (AOR: 2.01, 95% CI: 1.03, 3.93). CONCLUSIONS: The results highlight the importance of the family’s role in concurrent heroin use during MMT programs. The study’s findings may have implications for family-based interventions that address concurrent heroin use.